Clinical and Functional Characteristics of a New Phenotype of SMA Type I among a National Sample of Spanish Children: A Cross-Sectional Study - Beatriz de-; Javier Güeita-Rodríguez; Domingo Palacios-Ceña; Ángel Luis Rodríguez-Fernández (MDPI AG, 2023)
Spinal Muscular Atrophy (SMA) type I has classically presented extremely severe clinical features. New pharmacological treatments have led to a new phenotype of SMA. The aim of this study was to describe the current health and functional status of children with SMA. A cross-sectional study was conducted based on the STROBE guidelines. Patient questionnaires and standardized tools were used. A descriptive analysis was conducted establishing the proportions of subjects for each of the characteristics of interest. In total, 51 genetically confirmed SMA type I subjects were included. Fifty-seven percent received oral feeding, 33% received tube feeding and 10% combined both. Moreover, 21.6% had tracheostomies, and 9.8% needed more than 16 h/d ventilatory support. Regarding orthopedic status, 66.7% had scoliosis, and 68.6% had hip subluxation or dislocation. Up to 67% were able to sit independently, 23.5% walked with support and one child walked independently. Current SMA type I is a different entity from the classic phenotype but also from types II and III. In addition, no differences were found between SMA type I subgroups. These findings may enable the professionals involved in the care of these patients to improve their interventions in terms of prevention and rehabilitation measures for these children.